Cost analysis of childhood hematopoietic stem cell transplantation in Sichuan, China - Chen, Min; Liu, Yantao; Yang, Xue; Hong, Yu; Ni, Jiaqi (Frontiers in Public Health, 2023)
Objective: To analyze the inpatient cost of hematopoietic stem cell transplantation (HSCT) in children, so as to support clinical decision-making. Methods: Study population were children who received HSCT in a tertiary children's hospital (Sichuan, China) between January 1st, 2020 and December 31st, 2021. The median and interquartile range (IQR) of total cost at 100 days post transplantation were calculated. Subgroup analyses were conducted based on age, gender, transplantation types, and post-transplant complications. The cost differences between subgroups were analyzed to determine whether it had an impact on the total costs. Results: A total of 142 pediatric patients were included in the study with a total cost of 250,721.78 yuan (197,019.16- 315,740.52, 1 yuan equals to around 0.15 US dollars). Drug costs accounted for 51.85% of the total cost, followed by medical service costs (12.57%) and treatment expenses (12.24%). In terms of transplantation types, the cost of autologous transplantation was lower than that of allogeneic transplantation (115,722.98 yuan vs 256,043.99 yuan, P<0.05), and the cost of human leukocyte antigen (HLA) complete matched was lower compared with that of partial matched (213,760.88 yuan vs 294,044.84 yuan, P<0.05). As for post-transplant complications, cases with < 3 types of complications cost less than those with ≥ 3 types (212,893.25 yuan vs 286,064.60 yuan, P<0.05), and those with severity ≤ grade 2 cost less than those > grade 2 (235,569.37 yuan vs 280,061.58 yuan, P<0.05). Age and gender of patients did not lead to statistical differences in the total cost, while the transplantation types and post-transplant complications influenced the total cost. Conclusion: The total cost at 100 days post transplantation associated with HSCT treatment were substantial for pediatric patients. The HLA compatibility between donors and recipients, and post-transplant complications were important factors affecting the total cost.